Diabetes knowledge and glycemic control among type 2 diabetes patients at public hospitals in Debre Berhan, Ethiopia - Girma Deshimo Lema; Enguday Demeke Gebeyaw (PLoS ONE, 2025)
Background Diabetes mellitus is a growing global health issue, especially in low- and middle-income countries like Ethiopia. To the best of our knowledge, the impact of diabetes knowledge on glycemic control in Ethiopia has not been documented. This study assessed diabetes knowledge and its relationship with glycemic control among Type 2 diabetes (T2DM) patients in Debre Berhan, Ethiopia. Methods A cross-sectional study was conducted involving 380 patients diagnosed with T2DM who were receiving care at two hospitals in Debre Berhan from January 1 to March 30, 2024. Patients’ knowledge was assessed using the modified Diabetes Knowledge Questionnaire (DKQ-18), categorizing outcomes as either good or poor. Glycemic control was evaluated using hemoglobin A1c (HbA1c) levels. Logistic regression analyses were conducted to identify predictors of poor diabetes knowledge. Correlation analysis was used to evaluate the relationship between knowledge and glycemic control. Results Among the 380 participants, 75.2% were older than 45 years, and 51.3% were male. Overall, 62.4% of participants had poor knowledge of diabetes. Additionally, 72.6% had poor glycemic control, with HbA1C levels ≥7%. The mean average diabetes knowledge score was 7.9 (SD = 3.49) out of 18, and the median HbA1C was 8%. Diabetes knowledge was significantly associated (p < 0.05) with patients’ educational level, occupation, family history of diabetes, and glycemic control. The Spearman correlation coefficient between HbA1C and diabetes knowledge scores was -0.166 (p = 0.001), suggesting a weak but statistically significant inverse relationship between knowledge scores and HbA1C levels. Conclusions The study found that the majority of patients had a low level of diabetes knowledge. Enhancing diabetes education and identifying additional factors that influence glycemic control are crucial for achieving optimal diabetes management in Ethiopia. Public health initiatives should prioritize enhancing diabetes knowledge through targeted educational programs and resources to support effective diabetes management and achieve optimal glycemic control.